Physician intervention via knowledge management: using HL7 messaging to increase breast-screening uptake. (1st September 2010) - Baskaran, V.; Bali, R.K.; Arochena, H.; Naguib, R.N.G.; Wheaton, M.; Wallis, M.; Benson, T.; Wickramasinghe, N.
Healthcare strategists have realised the relevance and importance of Knowledge Management (KM) for clinical and healthcare environments. There has been a huge thrust in Information Technology (IT) driven KM projects in healthcare. Projects related to Electronic Patient Record (EPR) have been the focus of many of the healthcare projects being carried out around the world. The synergy between overlapping technologies and the need for semantic interoperability of disparate systems have revolutionised how knowledge, information and data is being exchanged across the healthcare realm. This project addresses the issues of KM by leveraging the available IT tools and technologies within approved and dedicated standards (for example, HL7) to increase breast-screening attendance in a regional setting in the UK.